1968
DOI: 10.1002/cber.19681010631
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside und verwandte Verbindungen, VI. Synthese der anomeren 2′‐Desoxy‐D‐ribopyranosyl‐uracile

Abstract: Bis‐O‐trimethylsilyl‐uracil (3), das mit Methyljodid oder Acetylchlorid selektiv N‐1‐substituierte Uracile bildet, reagiert in Gegenwart verschiedener Katalysatoren bei niedrigen Temperaturen mit den 2‐Desoxy‐D‐ribopyranosylchloriden 7 und 8 in guten Ausbeuten zu den acylierten α,β‐Nucleosiden 11 (p‐Toluat) bzw. 12 (p‐Nitro‐benzoat). Nach Entacylierung und Säulenchromatographie werden daraus 2′‐Desoxy‐α‐D‐ribopyranosyl‐uracil (α‐13) und sein β‐Anomeres β‐13 gewonnen, wobei α‐13 gegenüber der β‐Form in jedem Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In contrast, when heated at reflux in toluene with piperidinium acetate,15 20 gave a mixture of the two ketones 21 and 22 in approximately 70% yield. Exposure of isomer 22 to p-toluenesulfonic acid in toluene at reflux resulted in a 60% yield of the conjugated isomer 21. The physical data for compound 21 compare well with the reports in the literature;16 however, 22 could not be compared with previously synthesized material as no data are given,17 and the structure rests solely on our 7H NMR, IR, and UV spectra (see Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, when heated at reflux in toluene with piperidinium acetate,15 20 gave a mixture of the two ketones 21 and 22 in approximately 70% yield. Exposure of isomer 22 to p-toluenesulfonic acid in toluene at reflux resulted in a 60% yield of the conjugated isomer 21. The physical data for compound 21 compare well with the reports in the literature;16 however, 22 could not be compared with previously synthesized material as no data are given,17 and the structure rests solely on our 7H NMR, IR, and UV spectra (see Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
“…To a solution at 10 °C containing 4.68 g (9.3 mmol) of 1-O-acetyl-2,3,5-tri-O-benzoyl-d-D-ribofuranoside25 and 2.0 g (8.6 mmol) of bis(0-trimethylsilyl) [4-13C] uracil (10) in 100 mL of dry acetonitrile under a dry nitrogen atmosphere was added 1.6 g (6.1 mmol) of freshly distilled (from P2O5) stannic chloride in 50 mL of dry acetonitrile. The resulting solution was stirred at room temperature (22 °C) for 16 h and the solvent was removed at 22 °C under reduced pressure. The residue was dissolved in 300 mL of 1,2-dichloroethane and shaken with 250 mL of a saturated sodium bicarbonate solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Smith and Cook have shown that apocodeine (2) may be Oand N-dealkylated in vivo by rats to 1 and norapomorphine. 16…”
Section: Methodsmentioning
confidence: 99%
“…By some modifications of this sequence we have now prepared the 2'-hydroxy relative 18. Described below are the synthesis of 18 and the analgetic and other pharmacologic properties of16 and 18 and two analogs, 15 and 17.…”
mentioning
confidence: 99%